The Relationship between Corporate Governance and Audit Quality:UK Evidence - Deng, Xuan (2011)
This study examines the relationship between corporate governance characteristics (relating to the size, composition of independent members, financial expertise, meeting frequency of board of directors and audit committee) and audit quality. The absolute values of abnormal accruals estimated by Jones (1991) model are used as the proxy of audit quality. Based on data obtained from FTSE 250 between 2006 and 2010, the empirical findings suggest that there is a negative association between the size of boards of directors and audit quality. This study also indicates a positive relationship between audit committee meeting frequency and audit quality. While the results do not find that the independence and financial expertise of boards and audit committee have relations with audit quality. Consistent with many prior studies and agency theory, the results prove that effective corporate governance likely leads to higher audit quality, because effective corporate governance are able to improve internal control, maximize the interests of shareholders, and monitor the operating of management. The findings are of potential interest to policy makers, professionals and board of directors, especially on issues relating to audit quality.